2006
DOI: 10.1126/science.1129378
|View full text |Cite
|
Sign up to set email alerts
|

Observations of Biologically Generated Turbulence in a Coastal Inlet

Abstract: Measurements in a coastal inlet revealed turbulence that was three to four orders of magnitude larger during the dusk ascent of a dense acoustic-scattering layer of krill than during the day, elevating daily-averaged mixing in the inlet by a factor of 100. Because vertically migrating layers of swimming organisms are found in much of the ocean, biologically generated turbulence may affect (i) the transport of inorganic nutrients to the often nutrient-depleted surface layer from underlying nutrient-rich stratif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

12
139
5

Year Published

2007
2007
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 110 publications
(156 citation statements)
references
References 18 publications
12
139
5
Order By: Relevance
“…Kunze et al [2006] observed significantly elevated kinetic energy dissipation rates in the vicinity of aggregations of krill, and subsequently noted shear fluctuations at length scales up to one meter, significantly larger than the individual animals [Kunze et al, 2007]. By contrast, recent field measurements by Gregg and Horne [2009] and Lorke and Probst [2010] and numerical simulations by J.-L. Thiffeault and S. Childress (Stirring by swimming bodies, arXiv:0911.5511v1, 2010) all indicate negligible buoyancy flux due to animal swimming.…”
Section: Introductionmentioning
confidence: 81%
See 1 more Smart Citation
“…Kunze et al [2006] observed significantly elevated kinetic energy dissipation rates in the vicinity of aggregations of krill, and subsequently noted shear fluctuations at length scales up to one meter, significantly larger than the individual animals [Kunze et al, 2007]. By contrast, recent field measurements by Gregg and Horne [2009] and Lorke and Probst [2010] and numerical simulations by J.-L. Thiffeault and S. Childress (Stirring by swimming bodies, arXiv:0911.5511v1, 2010) all indicate negligible buoyancy flux due to animal swimming.…”
Section: Introductionmentioning
confidence: 81%
“…[3] A notable difference between the measurements of Kunze et al [2006] and subsequent investigations is that the former experiments were carried out on plankton during vertical migration. By contrast, the field measurements of schooling fish by Gregg and Horne [2009] and Lorke and Probst [2010] and the numerical simulations by Thiffeault and Childress (arXiv:0911.5511v1, 2010) are missing this behavioral component of animal swimming.…”
Section: Introductionmentioning
confidence: 99%
“…The role of biologically generated turbulence for vertical mixing of the ocean became the issue of a recent debate (Kunze et al 2007;Visser 2007a,b). Although this issue is not really a new one, it was brought into focus by a study of Kunze et al (2006), who observed strongly increased levels of turbulence during the ascent of dense swarms of krill performing diel vertical migration in the coastal ocean.…”
mentioning
confidence: 99%
“…2). We then used the model to examine the spatial distribution of sediment in Saanich Inlet, considering realistic cross-slope advection, u 5 0.77 km d 21 (Yahel et al 2008); vertical eddy diffusivity, e z 5 20 3 10 24 m 22 s 21 , which is in the middle of the range reported for Saanich Inlet (Kunze et al 2006); and settling velocity (w s ). The settling velocities (w s ) for silt and clay were estimated independently according to Stokes's law using particles and seawater density of 2.6 and 1.025 g cm 23 , respectively; viscosity of 0.015 dyne s cm 22 ; and mean particle diameter of 3 and 20 mm for clay and silt, respectively.…”
Section: )mentioning
confidence: 99%